Demokrasi Digital dan Polarisasi Politik: Strategi Pendidikan Kewarganegaraan dalam Membangun Civic Unity: Digital Democracy and Political Polarization: Citizenship Education Strategy in Building Civic Unity - Ahmad Muhamad Mustain Nasoha; Rafida Putri Parastuti; Naqiyyatul Aghni Nur Sya’ban; Zahrifah Rahmah (Litera Academica Publishing, 2025)
Civics Education (PKn) plays a crucial role in shaping citizens' political and social awareness, particularly amidst the challenges of increasingly sharp political polarization. This polarization often exacerbates social fragmentation and threatens societal integration in digital democracy. As the development of digital technology expands the public space for political discussion, it is crucial to explore how PKn can serve as an instrument for strengthening civic unity. This study aims to analyze the challenges faced by civics education in building unity amidst political polarization and to formulate strategies that can be implemented in the context of digital democracy. The results indicate that integrating technology-based approaches, developing critical thinking skills, and instilling the values of tolerance and constructive dialogue are effective strategies for strengthening civic unity. In conclusion, civics education that adapts to digital developments can be a solution to address the negative impacts of political polarization.